Diagnóstico do Programa ABC em Nova Crixás-Goiás - Láscar Alarcón, Luz Magdalena (2019)
Faced with international pressures, due to emissions of greenhouse gases (GHG) with globalized damages such as temperature warming, rainfall change, among others, Brazil has a relevant role, being one of the largest world producers of commodities, and the agricultural sector is one of the economic sectors that generate the most environmental impacts. In 2009, the Ministry of Agriculture, Livestock and Supply (MAPA) created a public policy entitled "Sector Plan for Mitigation and Adaptation to Climate Change for the Consolidation of a Low Carbon Economy in Agriculture: ABC Plan (Low Carbon Agriculture), as a way of proposing forms of agricultural production that contribute to the reduction of GHG. The purpose of this study is to analyze the ABC Program and how it affected the region of Nova Crixás, which is the municipality with the largest cattle herd in the state of Goiás and that was highlighted in the period from 2013 to 2018, due to the high amount of values contracted in this municipality, totaling R $ 96 million, specifically referring to the pasture recovery program (ABC Recuperação), which is part of the ABC Program and is responsible for financing loans to rural producers. The research method is qualitative and quantitative, with the collection of primary and secondary data, and in addition to the financial analysis of Central Bank data, the use of remote sensing was used as an analysis tool to verify the pastures before and after the ABC program between 2013 and 2018. The greatest difficulty for organizations is to associate an economically viable production model that is both sustainable. The public policy of the ABC Plan proposes a financing program to encourage producers to adopt low carbon technologies that are sustainable production processes and are necessary for the recovery of degraded pastures.